Georgian-Language Religious Literature Published in Israel - Abraham Mamistvalov - Guledani, Lali ("Intercultural Dialogues" Transactions, 2025)
Jews have lived in Georgia for many centuries. In the 1970s of the 20th century, they began a mass repatriation (“aliyah”) to their historical homeland—Israel. The initial years of this “aliyah” were characterized by severe economic and social problems for Georgian Jews. To settle in a new country, they had to overcome linguistic and everyday challenges. Despite these difficulties, Georgian Jews successfully engaged in literary activities. Works of various genres and themes were produced in the Georgian language, the acquisition and study of which are necessary for a complete presentation of Georgian-Jewish literary relations. Also interesting is the linguistic and literary study of Georgian-language publications produced in Israel, which can reveal similarities and differences, linguistic features, and innovations in literary expression methods that may be due to changes in residence and social environment. In Georgian-language literature published in Israel, religious works are of particular importance. Jews, wherever they lived, considered religious faith and the observance of religious obligations to be a sacred duty that saved this nation from destruction. While living in Georgia, they resided in separate neighborhoods, built synagogues, prayed, and strictly observed the rules and traditions of the Torah. In Israel, Georgians continue their traditional religious life, although they have more opportunities to enhance their religious awareness in the Promised Land alongside fellow Israelis. This was facilitated to some extent by Georgian-language religious works published in Israel, as most Georgian Jews knew only Georgian perfectly. Various types of religious works were published in Israel, including books of the Bible, elementary issues of the Torah, prophetic passages, basic prayers in Hebrew, information about prominent rabbis and Talmid khakhamim in the Georgian Jewish community, translations of prayers and mitzvot, explanations of the attributes and theology of Judaism, discussions of Judaism in modern conditions, halakhic rules in Georgian (שֻׁלְחָן עָרוּךְ), and more. Several books by the writer Abraham Mamistvalov have a religious nature, which are examined and characterized in this article, along with prayers, explanations, and notes. After analyzing the texts, it is noted that the religious aspect is particularly prominent and significant in the multi-thematic and multi-faceted work of Abraham Mamistvalov, represented by both translated and original works. The writer's goal is to assist representatives of the Georgian-speaking community in Israel in preserving and enriching their religious consciousness with practically applicable books and to facilitate the observance of customs and rituals established over centuries.